Positive electrode active material, positive electrode comprising same, and lithium secondary battery

By using a mixture of large-particle and small-particle lithium-nickel-based transition metal oxides in the positive electrode active material of lithium secondary batteries, the problems of particle fracture and cracking are solved, and excellent roll pressure density and high temperature life characteristics are achieved.

CN119768933APending Publication Date: 2025-04-04LG ENERGY SOLUTION LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380061431.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-26
Filing Date
2023-12-22
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The positive electrode active materials of lithium secondary batteries are prone to particle rupture and cracking during the manufacturing and charging/discharging process, resulting in reduced life characteristics and increased side reactions.

Method used

A mixture of large-particle lithium nickel-based transition metal oxide and small-particle lithium nickel-based transition metal oxide is used as the positive electrode active material, where the large-particle oxide is in the form of secondary particles, and the small-particle oxide is in the form of single particles or quasi-single particles, and the particle characteristics are controlled by a specific P value.

Benefits of technology

The particle breakage and cracks during the rolling process are reduced, the rolling density is improved, the side reaction with the electrolyte is reduced, and the high temperature life and output characteristics are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005281393490000161
    Figure BDA0005281393490000161
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material comprising a large-particle-size lithium nickel-based transition metal oxide and a small-particle-size lithium nickel-based transition metal oxide, in which the large-particle-size lithium nickel-based transition metal oxide is in the form of secondary particles, the secondary particles are aggregates of primary particles, and the primary particles are aggregates of secondary particles. The small-diameter lithium nickel-based transition metal oxide is in the form of at least one of a single particle formed of one nodule and a quasi-single particle that is a composite of 30 or less nodules, and wherein a P value defined by a shape correlation factor of a large-diameter particle and a specific surface area factor of a small-diameter particle is 1.00 or more. The positive electrode active material is applied to the positive electrode to provide a lithium secondary battery in which cracking of positive electrode active material particles is suppressed, thereby improving lifespan and output characteristics and reducing gas production.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to Korean Patent Application No. 10-2022-0184869, filed on December 26, 2022, the disclosure of which is incorporated herein by reference in its entirety. Technical Field

[0003] The present invention relates to a positive electrode active material for a lithium secondary battery, and a positive electrode and a lithium secondary battery comprising the positive electrode active material. Background Art

[0004] Lithium secondary batteries are generally composed of a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode and the negative electrode include active materials capable of intercalating and deintercalating lithium ions.

[0005] As positive electrode active materials for lithium secondary batteries, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2, LiMnO4, etc.), lithium iron phosphate compounds (LiFePO4), etc. have been used. Among them, lithium cobalt oxide has the advantages of high operating voltage and excellent capacity characteristics, but the price of cobalt as a raw material is high, and its supply is unstable, making it difficult to commercially apply it to large-capacity batteries. The structural stability of lithium nickel oxide is poor, making it difficult to obtain sufficient life characteristics. At the same time, lithium manganese oxide has excellent stability, but has the problem of poor capacity characteristics. Therefore, in order to compensate for the problems of lithium transition metal oxides containing Ni, Co or Mn alone, lithium nickel-based transition metal oxides containing two or more transition metals have been developed, and in particular, lithium nickel cobalt manganese composite oxides containing Ni, Co and Mn are widely used in the field of electric vehicle batteries.

[0006] Conventional lithium nickel cobalt manganese oxide is usually in the form of spherical secondary particles in which tens to hundreds of primary particles are aggregated. However, for lithium nickel cobalt manganese oxide in the form of secondary particles in which a large number of primary particles are aggregated, there is a problem that particle rupture may occur during the rolling process when manufacturing the positive electrode, causing the primary particles to fall off, and cracks to appear inside the particles during charging and discharging. When the particles of the positive electrode active material are broken or cracked, the contact area with the electrolyte increases, which increases the gas generation and active material degradation caused by the side reaction with the electrolyte, thereby reducing the life characteristics. Summary of the invention

[0007] [Technical issues]

[0008] The present invention aims to solve the above problems and to provide a positive electrode active material capable of suppressing particle breakage and cracking during electrode manufacturing and charge / discharge processes and having excellent rolling density.

[0009] In addition, the present invention provides a positive electrode and a lithium secondary battery including the above-mentioned positive electrode active material, thereby having a low cracking rate (fine powder generation rate) and thus reducing side reactions with electrolytes, which leads to improved high temperature life, output and high temperature storage characteristics.

[0010] [Technical solution]

[0011] In order to solve the above problems, according to one aspect of the present invention, there is provided a positive electrode active material, comprising: a large-particle lithium nickel-based transition metal oxide and a small-particle lithium nickel-based transition metal oxide, wherein the large-particle lithium nickel-based transition metal oxide is in the form of secondary particles, the secondary particles are aggregates of primary particles, and the small-particle lithium nickel-based transition metal oxide is in the form of at least one of a single particle and a quasi-single particle, the single particle is formed by one nodule, the quasi-single particle is a composite of 30 or less nodule, and wherein the P value defined by the following equation 1 is 1.00 or more:

[0012] [Equation 1]

[0013] P=(A L ×R L ×C L ) / B S

[0014] Among them, A L , R L and C L are the aspect ratio, roundness and convexity of large-particle lithium nickel-based transition metal oxides, B S is the BET specific surface area (m 2 / g) dimensionless number.

[0015] In order to solve the above problems, according to another aspect of the present invention, a positive electrode including the positive electrode active material of the present invention is provided.

[0016] In order to solve the above problems, according to another aspect of the present invention, a lithium secondary battery including the positive electrode of the present invention is provided.

[0017] [Beneficial Effects]

[0018] The positive electrode active material for lithium secondary batteries of the present invention includes a mixture of lithium nickel-based transition metal oxides in the form of single particles and / or quasi-single particles with excellent particle strength and lithium nickel-based transition metal oxides in the form of secondary particles, wherein the secondary particles are aggregates of primary particles, wherein these two types of particles meet specific conditions, thereby reducing the occurrence of particle breakage or cracks caused by rolling when manufacturing the electrode, and achieving an excellent rolling density level.

[0019] In addition, in the positive electrode active material for lithium secondary battery of the present invention, particle crushing can be minimized, thereby reducing the side reaction with the electrolyte and thus reducing the gas production. In addition, during the charging and discharging process, the change of the crystal structure can be minimized, thereby suppressing the degradation of the positive electrode active material and thus improving the high temperature life characteristics and high temperature storage characteristics. In addition, due to the low resistance increase rate, the output characteristics can be excellent. DETAILED DESCRIPTION

[0020] The terms or words used in the specification and claims of this application should not be construed as limited to their ordinary or dictionary meanings, but should be construed as meanings and concepts consistent with the technical spirit of the present invention based on the principle that the inventor can fully define the concepts of the terms to best describe his invention.

[0021] It should be understood that terms such as "include", "comprising" and "having" used herein are intended to indicate the existence of implemented features, numbers, steps, components or a combination thereof, but do not exclude the possibility of the existence or addition of one or more other features, numbers, steps, components or a combination thereof.

[0022] In the present disclosure, a "single particle" is a particle formed by a single nodule. In the present disclosure, a "nodule" refers to a particle unit, which can be a single crystal without crystal grain boundaries, or a polycrystal without obvious grain boundaries when observed using a scanning electron microscope (SEM) at a field of view of 5000 to 20000 times. In the present disclosure, a "quasi-single particle" refers to a particle that is a composite formed by 30 or less nodules.

[0023] In the present disclosure, "secondary particles" refer to particles formed by agglomeration of tens to hundreds of primary particles. More specifically, secondary particles are agglomerates of 50 or more primary particles.

[0024] The term "particle" used in the present disclosure may include any one or all of a single particle, a quasi-single particle, a primary particle, a particle segment, and a secondary particle.

[0025] In this disclosure, “D 50 ” refers to the particle size of 50% in the volume cumulative particle size distribution of the positive electrode active material powder. The average particle size D50 It can be measured using a laser diffraction method. For example, the positive electrode active material powder is dispersed in a dispersion medium, then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000), and irradiated with an ultrasonic wave of about 28 kHz with an output of 60 W. Thereafter, the average particle size can be determined by obtaining a volume cumulative particle size distribution diagram and then obtaining a particle size corresponding to 50% of the volume cumulative amount.

[0026] In the present invention, “aspect ratio”, “roundness” and “convexity” are obtained by using a scanning electron microscope (SEM) to obtain a two-dimensional image of the positive electrode active material particles and using an image analysis program to analyze the particles from the minimum particle size (D min , short diameter), maximum particle size (D max In the present invention, these values ​​refer to the average values ​​of tens to hundreds of particles, preferably 300 particles.

[0027] Here, aspect ratio, roundness, and convexity can be calculated by the following equations A to C:

[0028] [Equation A]

[0029] Aspect ratio = D min / D max

[0030] [Equation B]

[0031] Roundness = (4 × area) / (π × (D max ) 2 )

[0032] [Equation C]

[0033] Convexity = (convex circumference) / (actual circumference)

[0034] In the above equation C, the protrusion perimeter refers to the perimeter of the particle obtained by connecting the protrusions with straight lines in a two-dimensional particle, that is, the perimeter when the particle to be measured is wrapped by an elastic band. The actual perimeter is the perimeter of the particle obtained by connecting the actual perimeter lines of the particle.

[0035] Hereinafter, the present invention will be described in more detail.

[0036] Positive electrode active material

[0037] The positive electrode active material according to the present invention may include: a large-particle lithium nickel-based transition metal oxide and a small-particle lithium nickel-based transition metal oxide, wherein the large-particle lithium nickel-based transition metal oxide is in the form of secondary particles, the secondary particles are aggregates of primary particles, and the small-particle lithium nickel-based transition metal oxide is in the form of at least one of a single particle and a quasi-single particle, the single particle is formed by one particle segment, the quasi-single particle is a composite of 30 or less particle segments, and wherein the P value defined by the following equation 1 is 1.00 or more:

[0038] [Equation 1]

[0039] P=(A L ×R L ×C L ) / B S

[0040] Among them, A L , R L and C L They are the aspect ratio, roundness and convexity of large-particle lithium nickel-based transition metal oxides, B S is the BET specific surface area (m 2 / g) dimensionless number.

[0041] The present inventors have proposed that by mixing large-particle lithium nickel-based transition metal oxides in the form of secondary particles having advantages in energy density and small-particle lithium nickel-based transition metal oxides in the form of single particles and / or quasi-single particles having reduced particle breakage, the particle characteristics can have advantages in both active material particle breakage and energy density.

[0042] According to an embodiment of the present invention, the P value obtained by equation 1 may be greater than 1.00, preferably greater than 1.01, or greater than 1.02, preferably less than 2.50, less than 2.30, less than 2.10, or less than 2.05, and more preferably less than 2.01.

[0043] The P value represents the ratio of the aspect ratio, roundness and convexity of the large particle size lithium nickel-based transition metal oxide to the specific surface area of ​​the small particle size lithium nickel-based transition metal oxide, and takes into account the following facts: in the case of secondary particle form, due to the particle characteristics in which hundreds of primary particles aggregate to form aggregates, the particle shape plays a more important factor than the specific surface area in terms of cracking rate or rolling density, but in the case of single particle and / or quasi-single particle form, the specific surface area can play a more important factor than the particle shape because it is a form in which there are about 30 or less primary particles (i.e., particle segments).

[0044] That is, when the P value is 1.00 or more, it may mean that energy density, particle breakage, and cracking rate can be compensated. When the P value is less than 1.00, there are many secondary particles of irregular shapes, and therefore, gas may be seriously generated due to side reactions caused by particle breakage. In addition, there is a problem that life characteristics may deteriorate, or capacity and output characteristics may be poor due to low energy density.

[0045] In other words, even if the shape of the secondary particles consists only of those close to spherical, the above-mentioned problem may occur when the specific surface area of ​​the active material particles in the form of single particles and / or quasi-single particles to be mixed is large. Even if the shape of the secondary particles is not completely spherical, when the specific surface area of ​​the active material particles in the form of single particles and / or quasi-single particles is small, it can be compensated, thereby preventing the above-mentioned problem from occurring.

[0046] According to one embodiment of the present invention, the large-particle lithium nickel-based transition metal oxide may have an aspect ratio of 0.85 or more, a roundness of 0.85 or more, and a convexity of 0.935 or more. Here, the aspect ratio, roundness, and convexity may be values ​​obtained by photographing lithium nickel-based transition metal oxide particles using a scanning electron microscope and obtaining an image using an image analysis program, and may be an average value of about 100 or more particles.

[0047] The aspect ratio of the large-particle lithium nickel-based transition metal oxide can be greater than 0.87, greater than 0.88, greater than 0.90, or greater than 0.91, the roundness can be greater than 0.87, greater than 0.88, greater than 0.90, or greater than 0.91, and the convexity can be greater than 0.937, greater than 0.939, greater than 0.940, or greater than 0.941.

[0048] In addition, according to one embodiment of the present invention, the BET specific surface area of ​​the small-particle lithium nickel-based transition metal oxide can be 0.60 m 2 / g to 1.10m 2 / g. Preferably, its BET specific surface area can be 0.63m 2 / g or more, 0.65m 2 / g or above, or 0.66m 2 / g or above, can be 1.07m 2 / g or less, 1.05m 2 / g or less, or 1.03m 2 / g or less.

[0049] When the aspect ratio, roundness and convexity of the large-particle lithium nickel-based transition metal oxide and the BET specific surface area of ​​the small-particle lithium nickel-based transition metal oxide meet the above ranges, the particle characteristics of the mixed active material can be easily controlled so that the P value is above 1.00, thereby improving the performance of the electrode and the battery.

[0050] According to one embodiment of the present invention, the small-particle lithium nickel-based transition metal oxide may have an aspect ratio of 0.80 or more, a roundness of 0.80 or more, and a convexity of 0.900 or more. The aspect ratio of the small-particle lithium nickel-based transition metal oxide may be 0.81 or more, 0.82 or more, 0.83 or more, or 0.85 or more, the roundness may be 0.81 or more, 0.82 or more, 0.83 or more, or 0.85 or more, and the convexity may be 0.937 or more, 0.939 or more, 0.940 or more, or 0.941 or more.

[0051] In addition, according to one embodiment of the present invention, the BET specific surface area of ​​the large-particle lithium nickel-based transition metal oxide can be 0.40 m 2 / g to 0.60m 2 / g, preferably 0.42m 2 / g or more, 0.45m 2 / g or above, or 0.47m 2 / g or more, 0.57m 2 / g or less, 0.55m 2 / g or less, or 0.53m 2 / g or less.

[0052] The aspect ratio, roundness and convexity of small-particle lithium nickel-based transition metal oxides and the BET specific surface area of ​​large-particle lithium nickel-based transition metal oxides do not affect the P value and do not significantly affect particle breakage, but when the above ranges are met, the energy density can be increased, thereby contributing to performance improvement.

[0053] According to one embodiment of the present invention, the mixing weight ratio of the large-particle size lithium nickel-based transition metal oxide to the small-particle size lithium nickel-based transition metal oxide can be 90: 10 to 40: 60, preferably 85: 15 or less, 80: 20 or less, 50: 50 or more, or 60: 40 or more. Considering problems such as reduced life and increased gas generation caused by particle breakage, lack of conductive paths, slurry process problems, and increased linear pressure during rolling, the mixing weight ratio of the large-particle size lithium nickel-based transition metal oxide to the small-particle size lithium nickel-based transition metal oxide preferably meets the above range.

[0054] Meanwhile, the positive electrode active material of the present invention may include a lithium nickel-based transition metal oxide, and specifically, a lithium nickel-based transition metal oxide having a composition shown in the following Chemical Formula 1:

[0055] [Chemical Formula 1]

[0056] Li 1+x Ni a Co b M 1 c M 2 d O 2-e X e

[0057] Wherein, M 1 includes one or more selected from Mn and Al; M 2 includes one or more selected from the group consisting of W, Zr, Y, Ba, Ca, Ti, V, Mg, Ta, and Nb; X includes one or more selected from the group consisting of N, P, S, F, and Cl; 0 ≤ x ≤ 0.5, 0.5 ≤ a < 1, 0 < b ≤ 0.4, 0 < c ≤ 0.4, 0 ≤ d ≤ 0.05, and 0 ≤ e ≤ 0.05.

[0058] In Formula 1 above, M 1 is Mn, Al, or a combination thereof, preferably Mn or a combination of Mn and Al; M 2 can be at least one selected from the group consisting of Zr, W, Y, Ba, Ca, Ti, Mg, Ta, and Nb, and is preferably at least one selected from the group consisting of Zr, Y, Mg, and Ti, and more preferably Zr, Y, or a combination thereof. M 2 element is not necessarily included, but when included in an appropriate amount, it can play a role in promoting grain growth or improving the crystal structure stability during calcination. In addition, X is an anion substituting for the oxygen site and can include N, P, S, F, or Cl.

[0059] 1 + x represents the molar ratio of lithium in the lithium nickel-based transition metal oxide and can be 0 ≤ x ≤ 0.30, 0 ≤ x ≤ 0.20, or 0 ≤ x ≤ 0.15.

[0060] a represents the molar ratio of nickel among all metals other than lithium in the lithium nickel-based transition metal oxide, and can be 0.60 ≤ a < 1.00, 0.70 ≤ a < 1.00, 0.75 ≤ a ≤ 0.99, 0.80 ≤ a ≤ 0.99, 0.82 ≤ a ≤ 0.99, 0.84 ≤ a ≤ 0.99 or 0.86 ≤ a ≤ 0.99. Here, the value of a, that is, the content of nickel in the transition metal, can be 60 mol% or more, preferably 70 mol% or more, or 75 mol% or more. The higher the nickel content and the lower the cobalt content, the more problematic the amount of gas generated and the capacity retention rate may be. However, when the P value is satisfied, particle breakage can be reduced and the roll pressing density can be increased, resulting in slightly more synergistic effects, because the positive electrode active material with a high nickel content has high capacity and high output characteristics, but can offset the disadvantages.

[0061] b represents the molar ratio of cobalt among all metals other than lithium in the lithium nickel-based transition metal oxide, and can be 0 < b < 0.30, 0.01 ≤ b < 0.25, 0.01 ≤ b < 0.20 or 0.01 ≤ b ≤ 0.15.

[0062] c represents the molar ratio of M among all metals other than lithium in the lithium nickel-based transition metal oxide 1 and can be 0 < c < 0.30, 0.01 ≤ c < 0.25, 0.01 ≤ c < 0.20 or 0.01 ≤ c ≤ 0.15.

[0063] d represents the molar ratio of the M 2 element among all metals other than lithium in the lithium nickel-based transition metal oxide, and can be 0 ≤ d ≤ 0.05, 0 ≤ d ≤ 0.03 or 0 ≤ d ≤ 0.02.

[0064] e represents the molar ratio of element X among all non-metals other than oxygen in the lithium nickel-based transition metal oxide, and can be 0 ≤ e ≤ 0.05, 0 ≤ e ≤ 0.02 or 0 ≤ e ≤ 0.01.

[0065] Meanwhile, the lithium nickel-based transition metal oxide may also include a coating on the particle surface, and the coating contains one or more coating elements selected from Al, Ti, W, B, F, P, Mg, Ni, Co, Fe, Cr, V, Cu, Ca, Zn, Zr, Nb, Mo, Sr, Sb, Bi, Si and S.

[0066] When the coating is present on the surface of the lithium nickel-based transition metal oxide particles, the contact between the electrolyte and the lithium nickel-based transition metal oxide can be inhibited by the coating, thereby having the effect of reducing the elution of transition metals or the generation of gas caused by side reactions with the electrolyte.

[0067] Preferably, the coating layer may include Co as a coating element. When a coating layer containing Co is formed on the surface of small-size lithium nickel-based transition metal oxide particles in the form of single particles and / or quasi-single particles and / or large-size lithium nickel-based transition metal oxide particles in the form of secondary particles, an effect of improving output and an effect of suppressing side reactions with the electrolyte can be obtained.

[0068] Method for producing positive electrode active material

[0069] Next, a method for producing the cathode active material of the present invention will be described.

[0070] The method for manufacturing the positive electrode active material of the present invention comprises the following steps: (S1) adding a 1 A transition metal solution containing cations of the present invention, an alkaline aqueous solution and an ammonium solution are mixed and coprecipitated to prepare a positive electrode active material precursor; and (S2) the positive electrode active material precursor and a lithium raw material are mixed and heat-treated to prepare a positive electrode active material.

[0071] By the conditions of the coprecipitation reaction and the firing conditions (e.g., the firing temperature and time of the lithium raw material and the precursor), the manufactured positive electrode active material can be in the form of a single particle (formed by one grain segment) or a quasi-single particle (a composite of 30 or less grain segments), or in the form of a secondary particle (an aggregate of primary particles). The positive electrode active material of the present invention can be obtained by separately preparing a large-particle lithium nickel-based transition metal oxide and a small-particle lithium nickel-based transition metal oxide and then mixing them.

[0072] Hereinafter, each step of the method of manufacturing the positive electrode active material will be described in detail.

[0073] First, a material containing nickel (Ni), cobalt (Co) and M is prepared. 1 For example, the transition metal solution may include a nickel-containing raw material, a cobalt-containing raw material, and a M-containing raw material. 1 Raw materials, including M 1 The raw material may be a manganese-containing raw material and / or an aluminum-containing raw material.

[0074] Thereafter, a positive electrode active material precursor may be prepared by adding a complex forming agent containing ammonium cations and an alkaline aqueous solution to the transition metal solution and performing a coprecipitation reaction.

[0075] The nickel-containing raw material can be, for example, nickel-containing acetates, nitrates, sulfates, halides, sulfides, hydroxides, oxides, hydroxy oxides, etc., in particular, Ni(OH)2, NiO, NiOOH, NiCO3·2Ni(OH)2·4H2O, NiC2O2·2H2O, Ni(NO3)2·6H2O, NiSO4, NiSO4·6H2O, fatty acid nickel, nickel halides or combinations thereof, but are not limited thereto.

[0076] The cobalt-containing raw material can be a cobalt-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, oxyhydroxyl, etc., especially Co(OH)2, CoOOH, Co(OCOCH3)2·4H2O, Co(NO3)2·6H2O, CoSO4, CoSO4·7H2O or a combination thereof, but is not limited thereto.

[0077] The manganese-containing raw material can be, for example, manganese-containing acetates, nitrates, sulfates, halides, sulfides, hydroxides, oxides, oxyhydroxides or combinations thereof, specifically manganese oxides, such as Mn2O3, MnO2, Mn3O4, etc.; manganese salts, such as MnCO3, Mn(NO3)2, MnSO4, manganese acetate, dicarboxylic acid manganese salts, manganese citrate, fatty acid manganese salts; manganese oxyhydroxides, manganese chloride, or combinations thereof, but are not limited thereto.

[0078] The aluminum-containing raw material can be, for example, Al2O3, Al(OH)3, Al(NO3)3, Al2(SO4)3, (HO)2AlCH3CO2, HOAl(CH3CO2)2, Al(CH3CO2)3, aluminum halides, or combinations thereof.

[0079] The transition metal solution can be prepared by mixing a nickel-containing raw material, a cobalt-containing raw material and a M-containing raw material. 1 The raw materials are added to a solvent for preparation, wherein the solvent is particularly water, or a mixed solvent of water and an organic solvent (such as alcohol) that can be uniformly mixed with water, or an aqueous solution containing a nickel raw material, an aqueous solution containing a cobalt raw material and an aqueous solution containing M 1 Raw materials to prepare.

[0080] The complex forming agent containing ammonium cations can be, for example, NH4OH, (NH4)2SO4, NH4NO3, NH4Cl, CH3COONH4, (NH4)2CO3 or a combination thereof, but is not limited thereto. Meanwhile, the complex forming agent containing ammonium cations can be used in the form of an aqueous solution, wherein the solvent can be water, or a mixture of water and an organic solvent (specifically, alcohol, etc.) uniformly miscible with water.

[0081] The basic compound can be an alkali metal or alkaline earth metal hydroxide, such as NaOH, KOH or Ca (OH) 2, a hydrate thereof, or a combination thereof. The basic compound can also be used in the form of an aqueous solution, wherein the solvent can be water, or a mixture of water and an organic solvent (particularly, alcohol, etc.) uniformly miscible with water.

[0082] The basic compound is added to adjust the pH of the reaction solution, and the amount thereof added may be such that the pH of the metal solution is 8 to 12.

[0083] The coprecipitation reaction can be carried out at a temperature of 35°C to 80°C under an inert atmosphere such as nitrogen or argon.

[0084] Thus, it is possible to prepare a 1 A positive electrode active material precursor of a cation.

[0085] By the above method, nickel-cobalt-M 1 The hydroxide positive electrode active material precursor particles are precipitated in the reaction solution. By controlling the nickel-containing raw material, the cobalt-containing raw material and the M-containing raw material 1 The concentration of the raw materials can be such that the positive electrode active material precursor has a nickel (Ni) content of 70 mol % or more, 75 mol % or more, preferably 80 mol % or more, and more preferably 82 mol % or more in the total metal content. The precipitated positive electrode active material precursor particles can be separated and dried according to conventional methods to produce a positive electrode active material precursor.

[0086] Thereafter, the positive electrode active material precursor and the lithium raw material are mixed and heat-treated.

[0087] The lithium raw material may be a lithium-containing sulfate, nitrate, acetate, carbonate, oxalate, citrate, halide, hydroxide or oxyhydroxide, but is not particularly limited as long as it is soluble in water. Specifically, the lithium raw material may be Li2CO3, LiNO3, LiNO2, LiOH, LiOH·H2O, LiH, LiF, LiCl, LiBr, LiI, CH3COOLi, Li2O, Li2SO4, CH3COOLi or Li3C6H5O7, and any one or a mixture of two or more thereof may be used.

[0088] The positive electrode active material precursor and the lithium raw material may be mixed in a molar ratio of 1:1 to 1:1.30. The positive electrode active material precursor and the lithium raw material may be mixed in a molar ratio of, for example, about 1:1, about 1:1.05, about 1:1.07, about 1:1.10, about 1:1.5, about 1:1.20, or about 1:1.30, but is not limited thereto.

[0089] In the case of a high Ni-type NCM-based lithium composite transition metal oxide having a nickel (Ni) content of 70 mol % or more, the heat treatment may be performed at a temperature of 650° C. to 1000° C. The heat treatment may be preferably performed, for example, at a temperature of 700° C. to 925° C., and more preferably at a temperature of 750° C. to 910° C. The formation of the positive electrode active material powder in the form of a single particle and / or a quasi-single particle is affected by the heat treatment temperature conditions.

[0090] Therefore, the manufactured positive electrode active material can have reduced particle breakage and crystal structure strain during a roll-pressing process or during charging and discharging of a lithium secondary battery including the same, and can have improved initial resistance characteristics.

[0091] Heat treatment can be carried out in air or oxygen atmosphere for example 4 to 12 hours. Specifically, heat treatment can be carried out for example more than 4 hours, more than 6 hours, more than 8 hours, more than 10 hours, can be carried out for less than 12 hours, less than 10 hours, less than 8 hours, and less than 6 hours.

[0092] At the same time, when preparing 2 When a lithium nickel-based transition metal oxide containing a metal or a lithium nickel-based transition metal oxide containing a non-metal (e.g., X) for anion substitution at an oxygen site is to be prepared, a catalyst containing M may be additionally mixed during the coprecipitation reaction or in the firing step. 2 Metal raw materials and / or raw materials containing element X. In this case, the raw materials containing M 2 The raw material of metal can be M 2 The raw material containing the element X can be a lithium salt of X or an acid containing X.

[0093] On the other hand, when it is necessary to form a coating on the surface of the lithium nickel-based transition metal oxide, after the above-mentioned heat treatment, the following steps may be further performed: the lithium nickel-based transition metal oxide prepared by the heat treatment is mixed with the coating raw material, and then the two are heat-treated. In this case, the mixing may be performed by solid phase mixing or liquid phase mixing, and the heat treatment may be performed at an appropriate temperature according to the coating raw material. For example, the heat treatment of the coating process may be performed at a temperature of 200°C to 700°C or 300°C to 600°C, but is not limited thereto.

[0094] In addition, when the positive electrode active material powder of the present invention is manufactured, it is preferred that no water washing treatment is performed after the heat treatment. Conventionally, when a high nickel (Ni) type NCM-based lithium composite transition metal oxide is manufactured, a water washing process is generally performed after the heat treatment to reduce the content of lithium by-products. However, according to the research of the present inventors, it has been found that when a water washing process is performed in the production of lithium nickel-based transition metal oxides in the form of single particles and / or quasi-single particles, the surface properties of the lithium nickel-based transition metal oxide deteriorate during water washing, and thus the resistance increases. Therefore, when the positive electrode active material of the present invention is manufactured, it is preferred that no water washing is performed, but the remaining lithium on the surface of the lithium nickel-based transition metal oxide is consumed by a coating formation process. In this way, when the positive electrode active material is manufactured without cleaning the lithium nickel-based transition metal oxide, the resistance increase caused by surface defects can be suppressed.

[0095] positive electrode

[0096] The positive electrode of the present invention comprises the positive electrode active material of the present invention as described above. Specifically, the positive electrode comprises a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode active material powder of the present invention. Since the positive electrode active material powder has been described above, its detailed description will be omitted, and only the remaining components will be described in detail below.

[0097] The positive electrode current collector may include a highly conductive metal, and there is no particular limitation, as long as the positive electrode active material layer can be easily adhered thereto and is not reactive within the voltage range of the battery. The positive electrode current collector may be, for example, stainless steel, aluminum, nickel, titanium, heat-treated carbon, or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium or silver. Moreover, the positive electrode current collector may generally have a thickness of 3 μm to 500 μm, and microscopic irregularities may be formed on the surface of the current collector to improve the adhesion of the positive electrode active material. The positive electrode current collector may be used, for example, in various shapes, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.

[0098] If necessary, the positive electrode active material layer may optionally include a conductive material and a binder in addition to the positive electrode active material powder.

[0099] In this case, the positive electrode active material powder may be contained in an amount of 80 wt % to 99 wt %, more specifically 85 wt % to 98.5 wt %, based on the total weight of the positive electrode active material layer, and when included within the above content range, excellent capacity characteristics may be exhibited.

[0100] The conductive material is used to provide conductivity to the electrode, and any conductive material can be used without particular limitation, as long as it has electronic conductivity and does not cause chemical changes in the battery. Specific examples of conductive materials may include: graphite, such as natural graphite or artificial graphite; carbon-based materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; powders or fibers of metals such as copper, nickel, aluminum, and silver; conductive tubes, such as carbon nanotubes; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, and any one thereof or a mixture of two or more thereof may be used. The content of the conductive material may be 0.1 wt % to 15 wt % based on the total weight of the positive electrode active material layer.

[0101] Binder is used to improve the adhesion between positive active material particles and the adhesion between positive active material and current collector. Specific examples of binders may include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, polymethyl methacrylate, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, polyacrylic acid, hydrogen is replaced by Li, Na or Ca these polymers or its various copolymers, and one or more mixtures thereof can be used. Based on the gross weight of the positive active material layer, the content of the binder may be 0.1 wt % to 15 wt %.

[0102] In addition to using the above-mentioned positive electrode active material powder, the positive electrode can be prepared according to a conventional positive electrode preparation method. Specifically, the above-mentioned positive electrode active material powder and, if necessary, a binder, a conductive material and a dispersant can be dissolved or dispersed in a solvent to prepare a positive electrode slurry composition, which can be coated on a positive electrode current collector, and then dried and rolled to prepare a positive electrode.

[0103] The solvent may be any solvent commonly used in the art, for example, any one or a mixture of two or more of dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), dimethylformamide (DMF), acetone or water may be used. The amount of the solvent may be sufficient to dissolve or disperse the positive electrode active material, conductive material, binder and dispersant (considering the coating thickness and manufacturing yield of the slurry), and the viscosity of the slurry is allowed to exhibit excellent thickness uniformity in the subsequent coating process of preparing the positive electrode.

[0104] Alternatively, the positive electrode may be prepared by casting the positive electrode slurry composition on a separate support and then laminating a film peeled off from the support on a positive electrode current collector.

[0105] Electrochemical Devices

[0106] Next, the electrochemical device of the present invention will be described. The electrochemical device of the present invention includes the above-mentioned positive electrode of the present invention. Specifically, the electrochemical device may be a battery, a capacitor, etc., and more specifically, may be a lithium secondary battery.

[0107] Specifically, the lithium secondary battery includes a positive electrode, a negative electrode disposed opposite to the positive electrode, and a separator and an electrolyte disposed between the positive electrode and the negative electrode. Since the positive electrode is the same as above, its detailed description is omitted, and only the remaining components will be described in detail below.

[0108] In addition, the lithium secondary battery may optionally further include a battery container that accommodates an electrode assembly formed of a positive electrode, a negative electrode, and a separator, and a sealing member that seals the battery container.

[0109] In a lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector.

[0110] The negative electrode current collector is not particularly limited as long as it has high conductivity and does not cause chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, heat-treated carbon, copper or stainless steel surface-treated with carbon, nickel, titanium or silver, or aluminum-cadmium alloy can be used. In addition, the negative electrode current collector can generally have a thickness of 3 μm to 500 μm, and, similar to the positive electrode current collector, microscopic irregularities can be formed on the surface of the current collector to improve the adhesion of the negative electrode active material. The negative electrode current collector can be used in various shapes, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.

[0111] The negative electrode active material layer may optionally include a binder and a conductive material in addition to the negative electrode active material.

[0112] As the negative electrode active material, a compound capable of reversibly inserting and deinserting lithium can be used. Specific examples thereof may be: carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metal substances capable of alloying with lithium, such as silicon Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloy, Sn alloy, or Al alloy; metal oxides capable of doping and dedoping lithium, such as SiO β(0<β<2), SnO2, vanadium oxide and lithium vanadium oxide; or a composite comprising the metal substance and a carbonaceous material, such as a Si-C composite or a Sn-C composite, and any one thereof or a mixture of two or more thereof can be used. In addition, a metallic lithium film can be used as a negative electrode active material. In addition, low-crystalline carbon and high-crystalline carbon, etc. can be used as carbonaceous materials. Common examples of low-crystalline carbon can be soft carbon and hard carbon, and common examples of high-crystalline carbon can be irregular, planar, flaky, spherical or fibrous natural graphite or artificial graphite, floating (Kish) graphite, pyrolytic carbon, mesophase pitch-based carbon fibers, mesophase carbon microspheres, mesophase pitch and high-temperature sintered carbon, such as coke derived from petroleum or coal tar pitch.

[0113] The negative electrode active material may be contained in an amount of 80 wt % to 99 wt % based on the total weight of the negative electrode active material layer.

[0114] The binder is a component that helps to bind the conductive material, the active material and the current collector, wherein the binder is generally added in an amount of 0.1 wt % to 10 wt % based on the total weight of the negative electrode active material layer. Examples of binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile rubber, fluororubber and various copolymers thereof.

[0115] The conductive material is a component for further improving the conductivity of the negative electrode active material, wherein the amount of the conductive material added may be 10% by weight or less, preferably 5% by weight or less, based on the total weight of the negative electrode active material layer. The conductive material is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery, and may be, for example: graphite, such as natural graphite or artificial graphite; carbon black, such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers, such as carbon fibers and metal fibers; carbon fluoride; metal powders, such as aluminum powder and nickel powder; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or conductive materials such as polyphenylene derivatives.

[0116] The negative electrode active material layer can be prepared by dissolving or dispersing the negative electrode active material and optional binder and conductive material in a solvent to form a negative electrode slurry composition, coating the slurry composition on the negative electrode collector and drying. Alternatively, the negative electrode active material layer can be prepared by casting the negative electrode slurry composition on a separate support, and then laminating the film peeled off from the support on the negative electrode collector.

[0117] Meanwhile, in lithium secondary batteries, the separator separates the negative electrode from the positive electrode and provides a path for the movement of lithium ions, and any separator can be used without particular limitation, as long as it is generally used as a separator in lithium secondary batteries. In particular, it is preferred to use a separator having excellent moisture retention ability to the electrolyte and low resistance to the transmission of electrolyte ions. Specifically, a porous polymer film can be used, for example, a porous polymer film made of a polyolefin polymer (such as ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer and ethylene / methacrylate copolymer), or a laminated structure having more than two layers of the above-mentioned polymer can be used. Moreover, common porous nonwoven fabrics can be used, for example, nonwoven fabrics formed of high melting point glass fiber or polyethylene terephthalate fiber. In addition, a coated separator including a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a separator having a monolayer or multilayer structure can be selectively used.

[0118] In addition, the electrolyte used in the present invention may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte or a molten inorganic electrolyte that can be used to prepare a lithium secondary battery, but the present invention is not limited thereto.

[0119] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0120] Any solvent can be used as an organic solvent without particular limitation, as long as it can be used as a medium through which ions participating in the electrochemical reaction of the battery can move. Specifically, the organic solvent can be: an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone and ε-caprolactone; an ether solvent such as dibutyl ether or tetrahydrofuran; a ketone solvent such as cyclohexanone; an aromatic hydrocarbon solvent such as benzene and fluorobenzene; or a carbonate solvent such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) and propylene carbonate (PC); an alcohol solvent such as ethanol and isopropanol; a nitrile such as R-CN (wherein R is a linear, branched or cyclic C2 to C20 hydrocarbon group, and may include a double bond aromatic ring or an ether bond); an amide such as dimethylformamide; a dioxolane such as 1,3-dioxolane; or a sulfolane. Among these solvents, carbonate solvents are preferred, and a mixture of cyclic carbonates (e.g., ethylene carbonate or propylene carbonate) having high ion conductivity and high dielectric constant and low viscosity chain carbonate compounds (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) which can improve the charge / discharge performance of the battery is more preferably used.

[0121] The lithium salt may be any compound without particular limitation as long as it can provide lithium ions used in lithium secondary batteries. Specifically, the anion of the lithium salt may be selected from F - , Cl - Br - ,I - 、NO3 - 、N(CN)2 - 、BF4 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - At least one of the group consisting of, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2) 2. LiCl, LiI, LiB(C2O4)2, etc. The lithium salt is preferably used in a concentration of 0.1 to 2.0 M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, thereby excellent electrolyte performance can be exhibited, and lithium ions can be efficiently moved.

[0122] In order to improve the life characteristics of the battery, suppress the reduction of the battery capacity and increase the discharge capacity of the battery, in addition to the above-mentioned electrolyte components, the electrolyte may also include at least one additive, for example, halogenated alkylene carbonate compounds (e.g., difluoroethylene carbonate), pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glycol dimethyl ether, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N, N-substituted imidazolidinones, ethylene glycol dialkyl ethers, ammonium salts, pyrroles, 2-methoxyethanol or aluminum chloride. In this case, based on the total weight of the electrolyte, the content of the additive may be 0.1 wt % to 5 wt %.

[0123] Example

[0124] Hereinafter, embodiments of the present invention will be described in detail so that those skilled in the art can easily implement the present invention. However, the present invention can be implemented in various forms and is not limited to the embodiments described herein.

[0125] Example 1

[0126] Preparation of large-particle lithium nickel-based transition metal oxide, whose Ni:Co:Mn molar ratio is 8:1:1, is a secondary particle powder, which is an aggregate of primary particles, and has a short diameter to long diameter ratio (aspect ratio) of 0.94, a roundness of 0.93, a convexity of 0.943, and a BET specific surface area of ​​0.48m 2 / g. The small-particle lithium nickel-based transition metal oxide was prepared, and the Ni:Co:Mn molar ratio was 8:1:1, the powder was a single particle or quasi-single particle, and the ratio of the short diameter to the long diameter (aspect ratio) was 0.86, the roundness was 0.85, the convexity was 0.925, and the BET specific surface area was 0.80m 2 The large-particle-size and small-particle-size lithium nickel-based transition metal oxides were mixed at a weight ratio of 7:3 to prepare a positive electrode active material having a P value as shown in Table 1 below.

[0127] Examples 2 to 4 and Comparative Examples 1 to 4

[0128] The large particle size and small particle size lithium nickel-based transition metal oxides having particle size characteristics as shown in Table 1 below were mixed to prepare positive electrode active materials of Examples 2 to 4 and Comparative Examples 1 to 4 having P values ​​as shown in Table 1 below.

[0129] Experimental Example 1: Confirmation of particle characteristics of positive electrode active material

[0130] For each of the positive electrode active materials prepared in Examples 1 to 4 and Comparative Examples 1 to 4, the positive electrode active material particles were photographed at 800 magnifications using a scanning electron microscope (SEM, Hitachi, S-4800) to obtain an image of about 300 particles. The particles in the SEM image were two-dimensionalized by an image analysis program (Image J), ​​and the minimum particle size (D min , short diameter), maximum particle size (D max The measured values ​​were substituted into equations A to C below to obtain the average values ​​of aspect ratio, roundness and convexity, which are shown in Table 1 below.

[0131] [Equation A]

[0132] Aspect ratio = D min / D max

[0133] [Equation B]

[0134] Roundness = (4 × area) / (π × (D max ) 2 )

[0135] [Equation C]

[0136] Convexity = (convex circumference) / (actual circumference)

[0137] In the above equation C, the protrusion perimeter refers to the perimeter of the particle obtained by connecting the protrusions with straight lines in a two-dimensional particle, that is, the perimeter when the particle to be measured is wrapped by an elastic band. The actual perimeter is the perimeter of the particle obtained by connecting the actual perimeter lines of the particle.

[0138] In addition, the BET specific surface area (m 2 / g) was measured by the BET method and calculated from the amount of nitrogen adsorbed at liquid nitrogen temperature (77 K) using BELSORP-mino II of BEL Japan. The results are shown in Table 1 below.

[0139] In addition, the P value expressed in Equation 1 is also shown in Table 1 below.

[0140] [Equation 1]

[0141] P=(A L ×R L ×C L ) / B S

[0142] Among them, A L , R L and C L They are the aspect ratio, roundness and convexity of large-particle lithium nickel-based transition metal oxides, B S is the BET specific surface area (m 2 / g) dimensionless number.

[0143] [Table 1]

[0144]

[0145] Experimental Example 2: Rolling density of positive electrode active material

[0146] The rolling density (g / cm2) of each positive electrode active material prepared in Examples 1 to 4 and Comparative Examples 1 to 4 was measured using a densitometer (Caver Pellet Press). 3 Specifically, 3 g of each positive electrode active material prepared in the above-mentioned embodiments and comparative examples was subdivided and densely packed into a cylindrical support with a diameter of 13 mm, and then a pressure of 9 tons was applied to measure the rolling density (g / cm 3 ). The results are shown in Table 2 below.

[0147] In addition, for an area of ​​1 μm or less, a pressure of 6 tons was applied to the positive electrode active material using a caver pellet press, and then the amount of fine powder generated (volume %) was calculated using the value obtained from the particle size analysis (PSD).

[0148] [Table 2]

[0149] <![CDATA[Rolling density (g / cm 3 )]]> Amount of fine powder produced (volume %) Example 1 3.24 5.9 Example 2 3.31 3.4 Example 3 3.16 2.9 Example 4 3.22 4.1 Comparative Example 1 3.20 8.5 Comparative Example 2 3.26 4.4 Comparative Example 3 3.21 6.7 Comparative Example 4 3.25 10.0

[0150] Referring to Table 2, it can be seen that the roll density of the Examples satisfying the P value is superior to that of Comparative Examples 1 to 4, and the amount of fine powder generated in Comparative Example 4 having a relatively high roll density is also very high.

[0151] Experimental Example 3: Evaluation of high temperature storage characteristics

[0152] A pouch cell including a positive electrode and a carbon negative electrode was prepared, the positive electrode comprising each of the positive electrode active materials of Examples 1 to 4 and Comparative Examples 1 to 4, and then charged to 4.2 V. Then, the two electrodes (loading amount: 400 mg / 25 cm 2 ) and two separators were placed in an aluminum (Al) bag of 6×6 cm size and placed on the lower plate of a coin-type battery and fixed with a gasket. Thereafter, 400 μl of electrolyte (EC / EMC) was vacuum injected twice, and each side was vacuum sealed to a thickness of 0.5 cm. Here, vacuum sealing refers to sealing under single-cell vacuum sealing conditions of 95 kPa / 93 kPa. The coin-type half-cell manufactured as above was stored in a convection oven at 60°C for 10 weeks, and the amount of gas generated (volume change rate, %) was evaluated by comparing the change in battery volume. The results are shown in Table 3 below.

[0153] Experimental Example 4: Evaluation of high temperature life and resistance characteristics

[0154] A single cell including a positive electrode and a negative electrode was manufactured. In the case of the positive electrode, each positive electrode active material powder prepared in Examples 1 to 4 and Comparative Examples 1 to 4 was applied to a current collector and dried to prepare a positive electrode. In the case of the negative electrode, natural graphite and artificial graphite were mixed in a ratio of 5:5 and used as a negative electrode active material, and 95.6% by weight of the negative electrode active material, 0.9% by weight of the conductive material, and 3.4% by weight of the binder were used to prepare the negative electrode. The loading amount of the negative electrode was 10.7 mg / cm 2 , the N / P ratio of the negative and positive electrodes was fixed at 1.08.

[0155] The capacity retention rate (%) of the single cell including the positive electrode active material powder of Examples 1 to 2 and Comparative Examples 1 to 4 was measured by 300 cycles at a temperature of 45°C. When the life was evaluated under the above method and conditions, the voltage and current during discharge were used to calculate the resistance ((V0-V1) / I, where V0 is the discharge start voltage, V1 is the voltage after 60 seconds of discharge, and I is the applied current), and the resistance increase rate was calculated using the resistance after the cycle compared to the initial resistance. The results are shown in Table 3 below.

[0156] [Table 3]

[0157] Volume change rate (%) Capacity retention rate at 45°C (%) Resistance increase rate at 45°C (%) Example 1 112 94 120 Example 2 109 93 117 Example 3 107 92 114 Example 4 110 92 120 Comparative Example 1 121 92 129 Comparative Example 2 115 90 128 Comparative Example 3 118 92 126 Comparative Example 4 130 88 145

[0158] Referring to Table 3 above, for the batteries using the positive electrode active materials of Examples 1 and 2, the volume change rate after 4 weeks of storage is relatively lower than that of the batteries using the positive electrode active materials of Comparative Examples 1 to 4. This shows that when the positive electrode active material of the present invention is adopted, the high temperature storage characteristics of the battery are improved. In particular, in the case of Comparative Example 4, it can be seen that the cracking rate is high, and therefore, gas is seriously generated due to the side reaction with the electrolyte. In addition, it can be seen that the capacity retention rate of the single cell using the positive electrode active material of Examples 1 to 4 under 300 cycle conditions is 92% or more, while the capacity retention rate of the single cell using the positive electrode active material powder of Comparative Examples 1 to 4 is lower than the capacity retention rate. In addition, it can be seen that the resistance increase rate is at least 6% to 15% or more and greater, and therefore, the output performance is also excellent in the embodiment. That is, it can be seen that when the positive electrode active material of the present invention is adopted, the high temperature life and output characteristics are improved.

Claims

1. A positive electrode active material comprising: Large particle size lithium nickel-based transition metal oxides and small particle size lithium nickel-based transition metal oxides, in, The large-particle-size lithium nickel-based transition metal oxide is in the form of secondary particles, which are aggregates of primary particles. The small-particle lithium nickel-based transition metal oxide is in the form of at least one of a single particle and a quasi-single particle, wherein the single particle is formed by one particle segment, and the quasi-single particle is a composite of 30 or less particle segments, and Wherein, the P value defined by the following equation 1 is greater than 1.00: [Equation 1] P=(A L ×R L ×C L ) / B S Among them, A L , R L and C L are the aspect ratio, roundness and convexity of the large-particle lithium nickel-based transition metal oxide, B S The small-particle size lithium nickel-based transition metal oxide is m 2 The dimensionless number of the BET specific surface area measured in g.

2. The positive electrode active material according to claim 1, wherein The P value obtained from equation 1 ranges from 1.00 to 2.

50.

3. The positive electrode active material according to claim 1, wherein The large-particle lithium nickel-based transition metal oxide has an aspect ratio of 0.85 or more, a roundness of 0.85 or more, and a convexity of 0.935 or more.

4. The positive electrode active material according to claim 1, wherein The small-particle lithium nickel-based transition metal oxide has an aspect ratio of 0.80 or more, a roundness of 0.80 or more, and a convexity of 0.900 or more.

5. The positive electrode active material according to claim 1, wherein The BET specific surface area of ​​the large-particle lithium nickel-based transition metal oxide is 0.40 m 2 / g to 0.60m 2 / g.

6. The positive electrode active material according to claim 1, wherein The BET specific surface area of ​​the small-particle lithium nickel-based transition metal oxide is 0.60 m 2 / g to 1.10m 2 / g.

7. The positive electrode active material according to claim 1, wherein The lithium nickel-based transition metal oxide is represented by the following chemical formula 1: [Chemical formula 1] Li 1+x Ni a Co b M 1 c M 2 d O 2-e X e wherein, M 1 comprises one or more selected from Mn and Al; M 2 comprises one or more selected from the group consisting of W, Zr, Y, Ba, Ca, Ti, V, Mg, Ta, and Nb; X comprises one or more selected from the group consisting of N, P, S, F, and Cl; 0 ≤ x ≤ 0.5, 0.5 ≤ a < 1, 0 < b ≤ 0.4, 0 < c ≤ 0.4, 0 ≤ d ≤ 0.05, and 0 ≤ e ≤ 0.

05.

8. The positive electrode active material according to claim 1, wherein The nickel content in the transition metal of the large-particle lithium nickel-based transition metal oxide and the small-particle lithium nickel-based transition metal oxide is independently 70 mol % or more. 9 . A positive electrode comprising the positive electrode active material according to claim 1 . 10 . A lithium secondary battery comprising the positive electrode according to claim 9 .